Contingency and changing reality: Perspectives from Germany. Issue 3 (23rd July 2020) - Waltemathe, Michael
Abstract: The World Wide Web connects less and disconnects more. In Germany as in the United States, disconnecting factions digitize their ideologies and overnight multiply their adherents. Such forces of disruption are incessant. Appeal to constructivist theory reveals that beneath this destabilizing dynamic is awareness of contingency, the feeling of disempowerment in the face of an unpredictable and uncontrollable future. Religion has the potential for stabilizing, but religious leaders will need to reignite a faith in the future to make this happen.